Extra-oral and non-genital chronic herpes infection in an HIV-infected patient: A case report - Sasit Fungtrakoon (2019)
© 2018 Siriraj Medical Journal. Objective: To report a case of uncommon site of chronic herpes infection in an HIV-infected male. Case presentation: A 19-year-old Thai HIV-infected male who was diagnosed with chronic herpes simplex infection located on the scalp and face without lesion in oral and genital areas. Conclusion: Chronic herpes simplex infection is predominantly located in oro-genital regions and presented as ulcerative lesions that frequently recur in immunocompromised patients. The prevalence is not known and HIV infection is a major risk factor. Misdiagnosis is common and might lead to delay of treatment. Oral acyclovir is the first line of treatment, although resistance to acyclovir has been found to be increasing.